Growth and yield system for teak plantations (Tectona grandis L. f.) in Campeche, Mexico - Tamarit-Urias, Juan Carlos; De los Santos-Posadas, Héctor Manuel; Aldrete, Arnulfo; Valdez-Lazalde, José René; Maldonado, Hugo Ramírez; Guerra-De la Cruz, Vidal (Instituto de Ecología, A.C., 2019)
Forest management decisions are addressed using dynamic growth and yield equations, which predict the future forest dynamic as a function of stand-level attributes and providing information for decision-making in sustainable development. They are more widely used as practical tools in forestry and can be desirable for plantation management-planning. Teak (Tectona grandis L. f.) is an important commercial species in plantations from Mexico, although there is a lack of scientific knowledge as regards the management or modeling tools to support functional forest management decision making. In this study an explicit growth and yield system (G&YS) was developed for plantation of Teak in Campeche, Mexico. The G&YS was integrated for algebraic difference dynamic equations and they were fitted to pairs of dasometric variables of stem-mapped re-measurements plots. The G&YS components were selected according to the goodness-of-fit system, also the graphical analysis between actual and fitted values was used. Both analyses considered the statistic accuracy and biologically realistic predictions. The mortality function was associated with the initial planting density and also it was sensitive to the site index. The selected growth systems for the basal area and volume per hectare were based on Schumacher equation. For a site index of 18 m at a reference age equal to 7.5 years and forest rotation equal to 19-year, the global estimated yield was of 152.75 m3 ha−1, while for densities of 1,250 trees per hectare and 816 trees per hectare, the yields were 136.86 m3 ha−1 and 113.12 m3 ha−1, respectively. The G&YS generated allows estimating the total volume with bark per hectare under the specific local conditions of establishment, silvicultural management and site quality of the teak plantations analyzed.